The Effectiveness of the E-Pusluh Application and Factors Influencing Daily Data Reporting by Agricultural Extension Workers in Bangka Regency - ahmad yani; fournita agustina (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
This study aims to analyze the effectiveness of the e-Pusluh application and the factors influencing daily data reporting by agricultural extension workers in Bangka Regency. A quantitative approach with a survey method was employed. The respondents were agricultural extension workers who used the e-Pusluh application in Bangka Regency. Primary data were collected using a Likert-scale questionnaire and analyzed through descriptive statistics and Structural Equation Modeling-Partial Least Squares (SEM-PLS) using SmartPLS 4.0. The research variables included perceived ease of use, perceived usefulness, digital competence of extension workers, facilitating conditions, institutional support, and application effectiveness. The results showed that the effectiveness of e-Pusluh use was in the high category, with an average score of 4.05. Perceived ease of use and perceived usefulness were categorized as very high, while digital competence, facilitating conditions, and institutional support were categorized as high. The SEM-PLS results indicated that digital competence had a positive and significant effect on the effectiveness of e-Pusluh application use. The R-square value of 0.78 indicated that the model explained 78% of the variance in application effectiveness. Strengthening the digital competence of extension workers is therefore a key strategy to improve application-based daily data reporting.